Pace of modal shifts in internationalization processes within a firm - Galdino, Kátia de Melo; Rezende, Sérgio Fernando Loureiro; Lamont, Bruce T (Organizações & Sociedade, 2019)
Our understanding of the temporal dimension of the internationalization of the firm is incomplete at best. Based on this knowledge gap, this article analyzes how the internationalization processes within a firm can be differentiated according to the pace of modal shifts. We built a qualitative, retrospective longitudinal, embedded case of the internationalization of a Brazilian medium-sized firm that established a footprint in 16 foreign markets over nearly three decades. We find that its internationalization processes can be classified into three groups as far as pace is concerned: an Unmovable Internationalization Process, an Inert Internationalization Process and an Accelerated Internationalization Process. We then call attention to a mismatch between the pace of learning and the modal shifts in the firm’s internationalization processes. Further, we suggest a new picture of the internationalization of the firm by proposing the existence of a number of internationalization processes that unfold at distinct paces within a single firm.